2009
DOI: 10.1007/s11055-009-9148-0
|View full text |Cite
|
Sign up to set email alerts
|

Use of Noben (idebenone) in the Treatment of Dementia and Memory Impairments without Dementia

Abstract: Noben (idebenone) at a dose of 120 mg per day for six months was used in the treatment of 35 patients aged 60-86 years with Alzheimer's-type dementia, mixed dementia, and memory impairments not reaching the stage of dementia. Patients were assessed on the basis of data from somatic, neurological, and psychiatric investigations, as well as neuropsychological testing and a series of psychometric and other scales and tests, before and after treatment. Significant improvements in patients' conditions on the MMSE w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Out of six clinical trials, five trials showed beneficial effect of idebenone in AD while one study failed to show a protective effect in AD patients. Despite the successful trials, the regulatory body deemed the data as insufficient to support the therapeutic use of idebenone in AD [40][41][42][43][44]. It has to be noted that there is still some controversy in the literature whether idebenone is merely an antioxidant like CoQ10 or a pharmaceutical drug with entirely different functions [39].…”
Section: Oxidative Stress and Admentioning
confidence: 99%
“…Out of six clinical trials, five trials showed beneficial effect of idebenone in AD while one study failed to show a protective effect in AD patients. Despite the successful trials, the regulatory body deemed the data as insufficient to support the therapeutic use of idebenone in AD [40][41][42][43][44]. It has to be noted that there is still some controversy in the literature whether idebenone is merely an antioxidant like CoQ10 or a pharmaceutical drug with entirely different functions [39].…”
Section: Oxidative Stress and Admentioning
confidence: 99%
“…In a multicenter, randomized, double-blind, placebo-controlled study in AD patients, treatment with idebenone was effective in delaying memory impairments associated with AD, with no significant side effects (42). In a more recent study, treatment of AD patients with idebenone in the predementia stage resulted in short-and long-term memory improvements in 37% of the patients (427). On a concluding note, although the precise mechanism of action of ubiquinone remains unknown and it does not appear to alter learning and memory under normal physiological conditions (147), it appears to play a central role as an antioxidant molecule involved in restoring the redox balance necessary for improvement of cognitive dysfunction associated with a multitude of pathological conditions, especially AD.…”
mentioning
confidence: 98%
“…27 Beneficial effects of idebenone have been demonstrated in the treatment of several neurodegenerative diseases in which glial tissue is involved in the pathogenesis, including the Leber hereditary optic neuropathy. [28][29][30][31][32][33] Besides the antioxidant properties of idebenone, effects of the substance on expression of antiapoptotic proteins also have been described. 34,35 Oxidative stress is a pathological condition in which the rate of reactive oxygen species (ROS) production exceeds the body's antioxidative capacity.…”
mentioning
confidence: 99%